2015
DOI: 10.1007/s13277-015-3543-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of the long non-coding RNA AI364715 in gastric cancer and its clinical significance

Abstract: Long non-coding RNA (lncRNA), which is greater than 200 nucleotides, is a class of RNA molecules without protein coding function. In recent years, studies have shown that lncRNAs are associated with cancers. They are affecting the occurrence and development of cancers. However, the diagnostic significances of lncRNAs in gastric cancer are largely unknown. In this study, we focused on AI364715, one typical lncRNA. A total of 186 samples were collected from two cancer centers. To find the potential association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…For example, decreased expression of ncRuPAR significantly correlates with tumor invasion depth, lymph node metastasis, distant metastasis, tumor size and TNM stage in gastric cancer . A downregulation in the expression of AI364715, GACAT1, and GACAT2 in gastric cancer tissues; PCAT29 in prostate cancer; AC026166.2–001 and RP11‐169D4.1–001 in larynx squamous cell carcinoma; lncRNA‐LET and MEG3 in GBC tissues could also be used as a prognostic marker. The epigenetic changes in lncRNAs could also predict prognosis of the disease.…”
Section: Lncrnas In Cancer Prognosismentioning
confidence: 99%
“…For example, decreased expression of ncRuPAR significantly correlates with tumor invasion depth, lymph node metastasis, distant metastasis, tumor size and TNM stage in gastric cancer . A downregulation in the expression of AI364715, GACAT1, and GACAT2 in gastric cancer tissues; PCAT29 in prostate cancer; AC026166.2–001 and RP11‐169D4.1–001 in larynx squamous cell carcinoma; lncRNA‐LET and MEG3 in GBC tissues could also be used as a prognostic marker. The epigenetic changes in lncRNAs could also predict prognosis of the disease.…”
Section: Lncrnas In Cancer Prognosismentioning
confidence: 99%
“…Advances in the depth and quality of transcript me sequencing have revealed a range of lncRNAs classes dysregulated in various human diseases, particularly cancer (9)(10)(11). H19 is a member of a highly-conserved cluster of imprinted genes, and was the first lncRNA to be associated with cancer (12). Previous studies have indicated that H19 exhibits dysregulated expression in GC (13,14), hepatocellular carcinoma (15), bladder cancer (16), breast cancer (17) and esophageal cancer (18), and that itmay cause tumor promoting and suppressing effects (19).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that ncRuPAR may inhibit GC by regulating PAR1, serving as a potential marker for GC [70]. Another downregulated lncRNA in GC is AI364715, which was assessed in GC tissue, paired human healthy gastric mucosa and gastric precancerous lesions (dysplasia) tissue [71]. AI364715 expression was significantly more downregulated in GC than in noncancerous and dysplasia tissues, and closely linked to tumor size and differentiation, which suggests AI364715 as a potential biomarker for a GC diagnosis [71].…”
Section: Tissue Markersmentioning
confidence: 91%